Uma análise econométrica do comportamento da desigualdade de renda no Brasil - Santos, Luciano Balbino dos (2018)
Based on the Panel Data structure, this work investigates the behavior of income inequality in Brazil from two main objectives: to test the validity of the Kuznets Curve for the Brazilian economy and to analyze the impact of financial development on regional inequalities. For the first objective, the period considered is from 1999 to 2014 and for the second, from 1999 to 2009. With respect to the Kuznets Curve, the validation test begins with the Granger Causality Test between Gini and Income supplemented by estimates econometrics. The results indicate a bicausal relationship between the highlighted variables and point to a reality opposite to the Kuznets hypothesis, with the inequality falling in the first movements of the growth, but assuming an ascending trajectory when the income is evident. Regarding the second objective, the results indicate that there is empirical evidence that financial development reduces the income inequality between the units of the federation and between regions, but where financial development is more intense, the impact on the inequality is more significant.